ENERGI CELAH-PITA MATERIAL TiO2/KOMPLEKS LOGAM-KLOROFIL (M=Zn2+, Co2+) DARI DAUN SINGKONG (Manihot esculenta crant) (BANDGAP ENERGY OF MATERIAL OF TiO2/METAL-CHLOROPHYLL COMPLEX (M= Zn2+, Co2+) FROM CASSAVA LEAVES (Manihot esculenta crant)) - Arif Sulaiman; Imelda Hotmarisi Silalahi; Anis Shofiyani; Ari Widiyantoro; Harlia Harlia (Tanjungpura University, 2022)
Synthesis and characterization of TiO2 films sensitized with chlorophyll and metal-chlorophyll complex (M=Zn2+, Co2+) were carried out. Chlorophyll isolated from cassava leaves shows absorption peaks on the UV-Vis spectra in the Soret band area (415 nm) and Q band area (665 nm). The metal-chlorophyll complex was prepared from the reaction of the isolated chlorophyll and ZnCl2 (for Zn2+-chlorophyll); CoCl2.6H2O (for Co2+-chlorophyll) under reflux condition at 65 ºC with a mole ratio of 1:1. The UV-Vis spectra of the isolated products showed a hypsochromic shift to 410 nm and 660 nm for Zn2+-chlorophyll whereas the spectrum of the Co2+-chlorophyll product demonstrated the shifts to 403 nm and 661 nm. These hypsochromic shifts are proposed to be a metal-to-ligand charge transfer (MLCT) transition as a result of chlorophyll metalation. The FTIR spectra of chlorophyll and metal-chlorophyll complexes have a similar pattern despite changes in the absorption of vibrational energy in several functional groups. The absorption of the C=N group shifted from 1372 cm-1 to 1368 cm-1 for both of the complexes, the C=C group of aromatic shifted from 1451 cm-1 to 1447 cm-1 (Zn2+-chlorophyll) and from 1451 cm-1 to 1445 cm-1 (Co2+-chlorophyll), and the C=O group of ketones shifted from 1627 cm-1 to 1645 cm-1 (Zn2+-chlorophyll) and from 1627 cm-1 to 1646 cm-1 (Co2+-chlorophyll). The shift pattern of the absorption peaks on the FTIR spectra indicates the coordination of metal ions towards the N atom in the pyrrole ring in the porphyrin structure of the chlorophyll. When the isolated chlorophyll as well as the chlorphyll complexes was sensitized on the surface of TiO2, variation of bandgap energy was observed. The calculation using the Tauc Plot method resulted in the bandgap energy of films of TiO2 at 3.20 eV, TiO2/chlorophyll at 2.97 eV, TiO2/Zn2+-chlorophyll at 2.87 eV, and TiO2/Co2+-chlorophyll at 2.90 eV